The Impact of Servitization on Supply Chain Management in Aero-Engine Industry: Analysis of Rolls Royce’s Case Study - Mahmood, Othman Kareem (2012)
Objective: The objective of this dissertation is to examine how implementing servitization might affect supply chain management in aero engine industry. It aims to draw guidelines from the literature and a practical case study for optimisation of implementing servitization with respect to the three elements of supply chain management, to create value for the entire stakeholders. Methodology/design/approach: A qualitative methodology is used to approach this study, as the problem can be analysed critically to link between different variables of the dissertation. A single case study method is used due to the nature of the main question highlighted, which is (How). Data collected mainly from the journals and publications online. Rolls Royce, which is a second largest engine manufacturer company worldwide, was selected as a case study because it has a complex product, supply chain, broad install based units and an infrastructure of MR&O system. the main resource is the Official website to design the case study. Findings/Value: This dissertation found that implementing servitization would change the significance of supply chain management elements; Information flow infrastructure will gain the lion share in importance to link all elements and components and organise Risk management. Competitors are also considered as a supplier partner to create or deliver value. Settlement of Accounts between Banks is modified and benchmarked to organise MR&O and servitization between competitors, and gain fully reliability and availability as a global network, with maintaining their customers. Suggestions: Firms must consider reengineering the organisation and the supply network with servitization in accordance to the nature of the business. Future research should be on the entrepreneurs’ servitization rather than shifting of manufacturing to servitization, and focusing on the drawbacks of servitization. Key words: Servitization, Supply Chain, Supply Chain Management (SCM), Value Creation, Performance objectives, Aero-Engine, Maintenance, Repair, and Overhaul (MR&O).